Solar irradiance as the proximate cue for flowering in a tropical moist forest - Wright, S. Joseph; Calderón, Osvaldo (Biotropica, 2018)
We compared flowering times predicted by six possible proximate cues involving seasonal changes in rainfall and irradiance and flowering times observed over 30 years of weekly censuses for 19 tree and liana species from Barro Colorado Island (BCI), Panama. Hypotheses concerning variation in the timing and intensity of rainfall failed to predict flowering times in any species. In contrast, 10 to 12 weeks of consistent high levels of irradiance predicted flowering times well for eight species, and six or seven weeks of rapidly increasing levels of irradiance predicted flowering times well for two species. None of the six possible proximate cues predicted flowering times adequately for the nine remaining species. We conclude that high and increasing levels of irradiance are the proximate cues for flowering in many BCI species. The seasonal movements of the Intertropical Convergence Zone cause strong seasonal changes in cloud cover, atmospheric transmissivity, and irradiance reaching the BCI forest. Inter-annual variation in the timing of movements of the Intertropical Convergence Zone is the most likely cause of inter-annual variation in the timing of flowering in these species. Much work remains to be done as the physiological mechanisms linking flowering and irradiance are unknown and the proximate cues for flowering remain to be identified for many other BCI species.